Problems at social and psychological adaptation of students from rural areas to the conditions of urban environment. (The Journal of Psychology and Sociology, 2015)
The article examines and systematized the main problems of social and psychological adaptation of students from rural areas in conditions of urban environment, which are presented in the form of three intercon nected blocks. Based on the analysis of literature, the study of experience in the orga nization of social and psychological adaptation of students from rural areas to the urban environment in terms of Kazakhstan and foreign universities, the results of the sociological, psychological and psychophysiological research to develop a model of socio psychological adaptation of stu dents from rural areas to urban conditions environment and preparation of guidelines for the organization of this process, I have identified the prob lem of social and psychological adaptation of students from rural areas to the urban environment, which I joined in blocks.
Keywords: Sociopsychological adaptation; urban environment; the countryside; professional structure.